Impact of COVID-19 quarantines on clozapine-induced constipation: Experience of utilizing a clozapine-induced constipation protocol at a state forensic psychiatric facility - Bridgette M. Gleisner, PharmD; O. Greg Deardorff, PharmD, BCPP; Yifei Liu, BS Pharm, PhD; Megan G. Trout, PharmD; Joshua R. Wood, PharmD; Roger W. Sommi, PharmD, BCPP, FCCP; Niels C. Beck, PhD (American Association of Psychiatric Pharmacists, 2024)
Objective Since 2017, Fulton State Hospital (FSH) has implemented a clozapine-induced constipation protocol. In March 2020, FSH initiated unit quarantines to minimize the spread of coronavirus disease (COVID-19). The objective of this study was to evaluate the impact of these quarantines on medical referrals for constipation, the Bristol Stool Chart ratings, utilization of as-needed (PRN) laxatives, and adherence rates with scheduled constipation medication regimens. Methods Patients on the clozapine-induced constipation protocol from May 1, 2019 to December 31, 2020, were included, with 10-month pre- and mid-quarantine implementation. Data collected included patient demographics, primary psychiatric diagnosis, and outcome variables. Descriptive statistics and paired t-tests were performed. Results A total of 31 patients were included. Most were male (93.5%), with a median age of 40 years. The most common primary diagnosis was schizophrenia. Compared with the pre-quarantine implementation period, there were fewer medical referral contacts per person, less use of PRN laxatives, and slightly lower adherence rates to scheduled constipation medication regimens during the mid-quarantine implementation period. Conclusion Compared with the pre-quarantine implementation period, there were fewer medical referrals per person during the mid-quarantine implementation period.